ALAT MUSIK DIATONIS UNTUK MENGEMBANGKAN TINGKAT KONSENTRASI ANAK TUNAGRAHITA RINGAN - ROSALIATI, DEVI (Jurnal Pendidikan Khusus, 2015)
ABSTRACT The music recited from the instrument could influence the concentration even the children’s intellectual. Therefore, diatonic instrument could be applied to develop the concentration of mild mentally retardation children. In doing observation on 5th February, 2015 in SDLB-C AKW II Surabaya it indicated that the children’s concentrating ability did not fully develop well yet and the range of concentration was relatively short. As the learning ran the children seemed musing and did not care to their teacher. The mild mentally retardation children seemed to have disturbance in concentrating and very often they failed in learning. This research had purpose to analyze the influence of diatonic instrument to develop the concentration level of mild mentally retardation children in SDLB-C AKW II Surabaya. The kind of this research was experiment with Single Subject Research arrangement and A-B design. The subject of this research was mild mentally retardation children in SDLB-C AKW II Surabaya experiencing the concentration disturbance. Based on the analysis done it indicated that baseline phase (A) was done in 5 sessions for 5 minutes meeting. And intervention phase (B) was done in 10 sessions for 10 minutes meeting. Appropriate with the data analysis and the discussion it could be concluded that there was enhancement concentration which was done by the mild mentally retardation children after giving the activity of playing diatonic instrument.   Keywords: Diatonic instrument, concentration